A nationwide population analysis of antenatal and perinatal complications among nurses and nonmedical working women - Chun-Che Huang; Yu-Tung Huang; Ming-Ping Wu (Taiwanese Journal of Obstetrics & Gynecology, 2016)
Objective: Limited information is available on health issues during pregnancy and after childbirth among nurses, especially on a nationwide level. This study thus aimed to compare antenatal and perinatal complications between nurses and nonmedical working women in Taiwan. Materials and Methods: This nationwide population-based study was conducted using data from the Taiwan National Health Insurance Research Database. A total of 44,166 nurses and 442,107 nonmedical working women with full-time employment, aged 20–50 years, who gave birth to singletons were identified between 2007 and 2011. Logistic regression analyses (generalized estimating equation method) were used to compare risks between the two groups. Results: Multivariable analyses showed that nurses had a significantly higher risk of anemia [adjusted odds ratio (AOR) 1.37; 95% confidence intervals (CI), 1.31–1.44], placenta previa, and abruptio placentae (AOR, 1.13; 95% CI, 1.07–1.20), and pregnancy-associated hypertensive diseases and preeclampsia (AOR, 1.10; 95% CI, 1.03–1.18) during the antenatal period than nonmedical working women. Moreover, they also experienced an increased risk of malpresentation (AOR, 1.30; 95% CI, 1.26–1.34), dystocia (AOR, 1.09; 95%, CI 1.06–1.13), preterm delivery (AOR, 1.08; 95% CI, 1.03–1.13), premature rupture of membranes (AOR, 1.09; 95% CI, 1.05–1.14), and post-term delivery (AOR, 1.11; 95% CI, 1.07–1.16) during the perinatal period. Conclusion: Our nationwide population-based study revealed increased risks of antenatal and perinatal complications among nurses compared with those among nonmedical working women. The large-scale observation of the increased antenatal and perinatal complications draws attention to the health issues faced by nursing personnel who represent one of the most important workforces in the healthcare system.